Immunoprofiling of glial tumours of the neurohypophysis suggests a common pituicytic origin of neoplastic cells - Hagel, Christian; Buslei, Rolf; Buchfelder, Michael; Fahlbusch, Rudolf; Bergmann, Markus; Giese, Armin; Flitsch, Joerg; Luedecke, Dieter K.; Glatzel, Markus; Saeger, Wolfgang (Pituitary, 2017)
To analyse the antigen expression profiles of 27 cases of pituicytoma, spindle cell oncocytoma, and granular cell tumour of the sellar region concerning a common pituicytic origin of neoplastic cells.Material from 12 female and 15 male patients (13 granular cell tumours of the sellar region, 10 pituicytomas, four spindle cell oncocytomas) collected in the German Registry of Pituitary Tumours between 1993 and 2015 was re-evaluated according to the current WHO classification of tumours of the central nervous system and supplementary immunohistochemistry including S100-protein, CD56, CD68, thyroid transcription factor-1 (TTF-1), and Ki-67 was performed.S100-protein was detected in all 27 tumours and TTF-1 in all 16 tumours that were assessed. Vimentin was expressed in all 13 cases investigated whereas broad spectrum cytokeratin was not detected in any of 14 evaluated cases. GFAP was observed in nine out of 21 cases. 15 out of 17 investigated lesions showed some CD68 expression and five out of 14 cases were labelled with CD56 antibodies. Proliferative activity did not differ significantly between the three tumour subgroups although one primary and one recurrent pituicytoma showed exceptionally high Ki-67-proliferation indices of 15.3 and 12.7 %, respectively (means: granular cell tumour of the sellar region 2.0 %, pituicytoma 2.8 %, spindle cell oncocytoma 2.7 %).The study confirms and expands earlier data and is in line with the notion that the three tumour types are variants of pituicytoma.
EVALuna2:7362